Ecology of Cryptopygus sverdrupi (Insecta: Collembola) from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Biology, 1986)
Observations on the ecology of Cryptopygus sverdrupi Lawrence (Collembola, Isotomidae) were made with specimens from the Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica. At an elevation of 1600 m a.s.l. the species was numerous in association with the green alga Prasiola on gravel fields and in crevices of large boulders. The distribution of size-classes in field samples suggested that the population comprised several overlapping generations. Growth and development is probably very slow due to long winters and daily periods of subzero temperatures in their microhabitat during the summer. Specimens collected in mid-January had a mean supercooling point of-24.6°C with small individual variations. The lack of high supercooling points in the summer suggests that the springtails feed on a nuleatorfree diet. The ability to supercool was increased during prolonged starvation and acclimation at 0,-4 and-8°C. Glycerol and other potential low molecular weight cryoprotective substances were demonstrated in specimens acclimated at-4 and-8°C. The species possessed a relatively high tolerance to desiccation.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

New records of terrestrial arthropods from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Research, 1986)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Terrestrial invertebrates of Mühlig-Hofmannfjella, Dronning Maud Land - Sømme, Lauritz (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Dronning Maud Land; NARE 1984/85; leddyr; virvelløse dyr; zoologi

Cold Hardiness of Collembola at Signy Island, Maritime Antarctic - Sømme, Lauritz; Block, William (Oikos, 1982)
The cold hardiness of two Antarctic species of Collembola, Cryptopygus antarcticus Willem and Parisotoma octooculata (Willem), was studied in field fresh, starved and low temperature acclimated specimens at Signy Island, in the South Orkney Islands. Supercooling points of both species clearly fell in a high group (HG) and a low group (LG) with a division at ca. -15°C. Field fresh specimens mainly had HG supercooling points, while starvation at 5° and 15°C greatly increased the number of LG animals. Further evidence of the relation between supercooling and feeding status was obtained in C. antarcticus. Specimens fed moss turf homogenate almost entirely returned to HG supercooling points, indicating the presence of efficient nucleators in this substrate. In specimens fed purified green algae a high proportion of LG supercooling points was retained, which suggests a lack of nucleators in this kind of food. Increased ability of LG specimens to supercool was demonstrated in C. antarcticus following acclimation at -5°C, and in P. octooculata at 0°C. In C. antarcticus an increase in concentrations of cryoprotective substances took place at -5°C concurrent with the lowering of the mean supercooling point. The main substances of the multicomponent cryoprotectant system of this species were trehalose, mannitol and glycerol. Chill-coma temperatures of specimens collected in the field differed in C. antarcticus and P. octooculata with mean values of -8.3° and -4.8°C, respectively. P. octooculata was less resistant to anaerobic conditions than C. antarcticus. All specimens of the former species were killed within 8 d in nitrogen at 0°C, while ca. 30% of C. antarcticus specimens survived after 28 d.
Publisher: [Nordic Society Oikos, Wiley]
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Supercooling in two Antarctic arthropods from Bouvetøya - Sømme, Lauritz (Bouvetøya, South Atlantic Ocean : results from the Norwegian Antarctic Research Expeditions 1976/77 and 1978/79, 1981)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Terrestrial arthropods from Vestfjella, Dronning Maud Land (Acari, Collembola), with notes on their taxonomy - Sømme, Lauritz (Insect Systematics & Evolution, 1980)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi